2006
DOI: 10.1111/j.1601-6343.2006.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the 3D measurement of postoperative swelling following orthognathic surgery

Abstract: The 3D laser-scanning device and the method described was a reliable and accurate measure of facial swelling following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 36 publications
0
55
0
6
Order By: Relevance
“…1 Therefore, the present study analyzes the short-term soft tissue changes, and the rationale for recording changes 2 months after surgery was based on the assumption that most of the postoperative swelling had been resolved by then. 4 Kau et al 21 observed that 1 month after bimaxillary surgery the soft tissues had obtained 82% of the contour they had 6 months after surgery, and during the following 2 months they changed only by 6%. Potential relapse of the surgical correction might still not be fully expressed, but it was assumed to be moderate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therefore, the present study analyzes the short-term soft tissue changes, and the rationale for recording changes 2 months after surgery was based on the assumption that most of the postoperative swelling had been resolved by then. 4 Kau et al 21 observed that 1 month after bimaxillary surgery the soft tissues had obtained 82% of the contour they had 6 months after surgery, and during the following 2 months they changed only by 6%. Potential relapse of the surgical correction might still not be fully expressed, but it was assumed to be moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Potential relapse of the surgical correction might still not be fully expressed, but it was assumed to be moderate. 21 The long-term response will be addressed in a future study. The variability in soft tissue changes (Figure 3) likely reflects the difference in the initial skeletal morphology and, accordingly, the skeletal changes as well.…”
Section: Discussionmentioning
confidence: 99%
“…surgical treatment, evaluation of postoperative swelling, 3D prefabricated archwires, research, and distinction between different syndromes involving craniofacial deformities. 4,5 3D imaging using a laser scanning system proved reliable over 3 minutes and 3 days, with accuracy within 0.85 mm. 6 A recent in vitro study using a photogrammetric tool for 3D acquisition showed a system error within 0.2 mm.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Since 3D scanning enables not only linear measures of outcome of orthog nathic surgery to be determined, but also volumetric changes, it means that the effect of factors such as post operative period and differing pharmacological interventions on facial swelling follow ing surgery can also be assessed. 32,33 Where patients require facial recon struction after tissue loss, as a result of trauma or malignancy, 3D scanning techniques can be used to map the area of deformity, mirror the area from the unaffected opposite side of the face and via rapid prototyping, recreate a facial prosthesis. 34 …”
Section: Orthognathic and Craniofacial Surgerymentioning
confidence: 99%